RELAPSES AFTER RADICAL SUBCUTANEOUS/SKIN-SPARING MASTECTOMY WITH SIMULTANEOUS RECONSTRUCTION IN BREAST CANCER - A. D. Zikiryakhodzhayev; E. A. Rasskazova; A. Yu. Tukmakov; I. M. Shirokikh (Исследования и практика в медицине)
Objective. To evaluate 3‑year disease-free survival in patients with breast cancer who underwent radical subcutaneous/skin-sparing mastectomy with simultaneous reconstruction.Patients and methods. The article analyzes 472 patients diagnosed with breast cancer who underwent radical subcutaneous/skin-sparing mastectomy in combined or complex treatment. In the Department of Oncology and reconstructive plastic surgery of the breast and skin radical skin mastectomy was performed in 255 (54.1%) and 217 (45.9%) patients with radical subcutaneous mastectomy. Reconstruction was carried out by autotissues, expanders, followed by replacement with endoprostheses, as well as a combination of flaps and endoprostheses. The mean age of patients was 43.8 ± 2.2 (18–73) years. In 32.3% of cases patients were in the age group up to 40 years.Results. In 9 (1,7 ± 0,6%) of patients diagnosed with a recurrence of breast cancer, herewith in 5 cases of local and in 4 cases of regional recurrence (metastases in the infraclavicular lymph nodes).Treatment of recurrences of breast cancer was as follows: in two cases polychemotherapy courses were conducted, in 6 cases operations were performed — excision of relapse in the breast (3) and subclavian lymphadenectomy (1), removal of the reconstructed gland (2), in 1 case — radiation therapy.In 13% relapses of breast cancer were diagnosed at stage III of breast cancer, the lowest percentage of relapse 0.7% at stage III. In luminal type A recurrence of breast cancer was diagnosed in 1.8%, in luminal B in 2.4%, in triple negative type — 2.5%, in luminal B Her2 positive — 2.7%. Metastases of breast cancer in our group of patients were diagnosed in 22 (4.7 ± 0.9%) patients. The highest percentage of long-term metastasis in our study revealed — 12.5% at stage III, the lowest percentage of 2.8 at stage I breast cancer. 3‑year overall survival of breast cancer patients in our group was 97.8% (n = 269).Conclusion. Radical subcutaneous/skin-sparing mastectomies with simultaneous reconstruction are radical in the oncological plan of treatment and improve the quality of life in patients with breast cancer.